GAMBARAN KEPUASAN KELUARGA PASIEN TENTANG PELAYANAN KESEHATAN DI RUANGAN HIGH CARE UNIT (HCU) - Muslim " "; Yulia Irvani Dewi; Arneliwati " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The purpose of this study was to determine the satisfaction of the patient's family describe of health care in the HCU. The research method was descriptive, to expressed satisfaction about the patient's family health services in the HCU Dr. RM. Pratomo Bagan Siapi-api Rokan Hilir involving 30 respondents. The sampling method wasaccidental sampling. Measuring tool used was questionnaire that has been tested for validity and reliability. Univariate analysis was used. The results showed that the majority of respondents were early adulthood (96.7%), male (53.3%), high school (43.3%), entrepreneur (53.3%), respondents relationship the patient was a child (56.7%), long us stay patient at the HCU 2 days (50%). Based on the level of satisfaction obtained category of respondents who are satisfied as much as 16 people (53.3%) and the response was not satisfied as many as 14 people (46.7%). Results of this study recommend nurses can perform a variety of management satisfaction about the patient's family health services in the HCU. Keywords: satisfaction, health services, HCU. Reference:38 (2004-2014)